Effect of Gastrointestinal Digestion on the Bioaccessibility of Phenolic Compounds and Antioxidant Activity of Fermented Aloe vera Juices - Ruth B. Cuvas-Limon; Pedro Ferreira-Santos; Mario Cruz; José A. Teixeira; Ruth Belmares; Clarisse Nobre (MDPI AG, 2022)
Plant-based beverages are enriched by the fermentation process. However, their biocompounds are transformed during gastrointestinal digestion, improving their bioaccessibility, which is of primary importance when considering the associated health benefits. This study aimed to evaluate the effect of in vitro gastrointestinal digestion on phenolic compound bioaccessibility and antioxidant activity of novel Aloe vera juices fermented by probiotic Enterococcus faecium and Lactococcus lactis. Aloe vera juices were digested using the standardized static INFOGEST protocol. During digestion, phenolic compounds and antioxidant activity (DPPH, ABTS, and FRAP) were accessed. The digestion process was seen to significantly increase the total phenolic content of the fermented Aloe vera juices. The fermentation of Aloe vera increased the bioaccessibility of juice biocompounds, particularly for kaempferol, ellagic acid, resveratrol, hesperidin, ferulic acid, and aloin. The phenolics released during digestion were able to reduce the oxidative radicals assessed by ABTS and FRAP tests, increasing the antioxidant action in the intestine, where they are absorbed. The fermentation of Aloe vera by probiotics is an excellent process to increase the bioavailability of beverages, resulting in natural added-value functional products.